Geothermobarometer based on coexisting garnet-orthopyroxene-plagioclase-quartz equilibria (Journal of Nepal Geological Society, 2016)
The garnet-orthopyroxene-plagolcase-quartz pairs are commonly found in the assemblages of basic granulites/charnockite and hence are suitable for estimating equilibrium temperature and pressure of most metamorphic rocks. The temperature based on garnet-orthopyroxene Fe-Mg exchange reaction and pressure based on net transfer reaction of garnet-orthopyroxeneplagioclase- quartz equilibria, mainly based on reactions, using the equation given by different workers. i. 1/2 Ferrosilite + 1/3 Pyrope = 1/2 Enstatite + 1/3 Almandine. ii. Ferrosilite + Anorthite = 2/3 Almandine + 1/3 Grossularite + Quartz iii. Enstatite + Anorthite = 2/3 Pyrope + 1/3 Grossularite + Quartz. The author developed software in visual basic with the executable code MPET3.EXE